Analisis Yuridis Pendekatan Restoratif Berbasis Kearifan Lokal pada Tindak Pidana Ringan - Herdy Pratama Susantyo; Ahmad Saifuddin; Ahmad Ferdi Hasan (Lembaga Yasin AlSys, 2025)
The limited number of studies on the integration of local wisdom into the application of restorative justice for minor criminal offenses forms the background of this research, despite the significant potential of such an approach to strengthen social legitimacy and reduce the burden on the formal criminal justice system. This study aims, through a normative juridical perspective, to: (1) analyze the normative support and legal boundaries within existing positive law instruments; (2) formulate juridical parameters that allow local wisdom to be considered a legitimate element in restorative justice mechanisms; and (3) propose policy recommendations to strengthen the normative framework. The method employed is normative juridical analysis using the statute approach and conceptual approach. Primary legal sources include Prosecutorial Regulation No. 15 of 2020, National Police Regulation No. 8 of 2021, and the new Criminal Code (Law No. 1 of 2023), while secondary and tertiary legal materials were obtained through legal literature and official legal databases. Data were analyzed using content analysis and legal interpretation through grammatical, systematic, and teleological methods. The findings indicate that while Prosecutorial Regulation No. 15 of 2020 has opened space for case dismissal based on restorative justice, it does not explicitly accommodate local wisdom values, potentially creating disharmony with the principle of legality and provisions in the Criminal Procedure Code. Moreover, regulatory inconsistencies at the village law level and ambiguities in classical literature regarding the scope of restorative justice were identified. The main conclusion of this study is the urgent need to draft or revise technical guidelines that explicitly regulate the integration of local wisdom as a valid juridical consideration within restorative justice mechanisms. The implications of this study are both theoretical enriching the literature on legal culture and restorative justice, and practical in enhancing the effectiveness of legally sound and socially accepted resolutions of minor offenses. This research also opens avenues for future studies with empirical and implementation-based approaches across different regions.